PROFILE OF PATIENTS PRESENTING TO THE DEPARTMENT OF VITREORETINAL SURGERY AND OCULAR TRAUMA AT THE UNIVERSITY EYE CLINIC - A TWO-YEAR RETROSPECTIVE STUDY: Retrospective Epidemiological Study of Presening Patients at the Department of Vitreoretinal and Ocular Trauma in a Tertiary Center - Kovacevic, Igor; Mirkovic, Jelena; Kristina; Pac, Cristina Patricia; Vasilijević, Jelena (Medical Research, 2023)
Introduction/Aim: Vitreoretinal diseases can lead to permanent vision loss. The aim of our study was to present frequency, demographics and treatment options of patients hospitalized and treated at the tertiary healthcare Department of Vitreoretinal Surgery and Eye Trauma in a two-year period. Material and Methods: The retrospective study was conducted at the Eye Clinic, University Clinical Center of Serbia in Belgrade, Serbia in the period from November 30, 2020 to December 4, 2022. Demographic, seasonality and treatment method data were collected from „Heliant“ healthcare software and subsequently interpreted. Results: During the study period, a total of 1295 patients were hospitalized. Cataract was the most common reason for hospitalization (n=355, 27.4%), followed by ocular trauma (n=303, 23.4%) and rhegmatogenous retinal detachment (n=287, 22.2%). The majority of patients with eye trauma (n=125, 41.2%, p˂0.001) were between 19 and 44 years old. Male predominance was found in ocular trauma (n=261,86.1%, p˂0.001), and also in patients hospitalized for rhegmatogenous retinal detachment surgery (n=166, 57.8%, p˂0.001) and surgery for complications of proliferative diabetic retinopathy (n=41, 71.9%, p˂0.001). Patients aged between 45 and 64 years were at the highest risk (n=136, 47.4%, p˂0.001) and vitrectomy was performed more often in treatment of rhegmatogenous retinal detachment (n=193, 67.2%, p˂0.001). Rhegmatogenous retinal detachment was most common in autumn (n=103, 35.9%, p˂0.001). Conclusion Further studies focusing more on some of the pathologies included in this study may be beneficial for a better understanding of epidemiology, preventive measures, and optimal treatment methods.